Techniques and methodologies for power quality analysis and disturbances classification in power systems: a review - Granados-Lieberman, D.; Romero-Troncoso, R.J.; Osornio-Rios, R.A.; Garcia-Perez, A.; Cabal-Yepez, E. (IET generation, transmission & distribution, 2011)
The relevance of power quality (PQ) issues has recently augmented because of the increased use of power electronic equipment, which results in a voltage deviation and current waveforms. The PQ monitoring is covered by two main subjects: the development of PQ indices to quantify the power supply quality and the electrical disturbances detection such as harmonics, sags, swells, etc., which allows knowing the conditions of the electric power systems. In this study, a review of techniques and methodologies developed for PQ analysis and power disturbance classification is presented in order to show their major characteristics.